EX-POST ASSESSMENT OF MERGER EFFECTS: THE CASE OF PFIZER AND PHARMACIA (2003) - LEHEYDA, Nina; BESCHORNER, Patrick; HÜSCHELRATH, Kai (Journal of Advanced Research in Law and Economics; Vol 2 No 1 (2011): JARLE Volume 1 Issue 1(3) Summer 2011, 2017)
The paper studies the effects of the Pfizer and Pharmacia (2003) merger on competition in the Swiss pharmaceutical market and compares the assessment of the Swiss Competition Commission (COMCO) with the post-merger market developments. We find that the merger has had a miniscule impact on the Swiss pharmaceutical market. This has primarily to do with the fact that the product portfolios of both companies have shown no or only slight overlaps. In both cases of potential anticompetitive effects, the companies successfully proposed to divest some of their assets in order to prevent a further strengthening of their dominant position. The remedies included products in the development phase which were not available on the market at the time of the decision.
Keywords: mergers, ex-post evaluation, pharmaceutical markets